2021
DOI: 10.1287/mnsc.2020.3675
|View full text |Cite
|
Sign up to set email alerts
|

Competition for Context-Sensitive Consumers

Abstract: When preferences are sensitive to context, firms may influence purchase decisions by designing the environment of consumption choices. This paper studies how competitive retailers optimally design their product line if preferences at the store depend on whether the choice set draws consumer attention to the quality or price of a product. Before making a purchase decision, a consumer chooses among retailers without (fully) anticipating that her preferences at the store are malleable. We show that this setup can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Other articles in this vein include Herweg et al (2017), Johnson (2017), Helfrich and Herweg (2020), Apffelstaedt and Mechtenberg (2021), Dertwinkel‐Kalt and Köster (2022), and our companion work in Inderst and Obradovits (2020). Notably, the present contribution builds on our earlier framework in Inderst and Obradovits (2020), where we also study retail competition with salient‐thinking consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Other articles in this vein include Herweg et al (2017), Johnson (2017), Helfrich and Herweg (2020), Apffelstaedt and Mechtenberg (2021), Dertwinkel‐Kalt and Köster (2022), and our companion work in Inderst and Obradovits (2020). Notably, the present contribution builds on our earlier framework in Inderst and Obradovits (2020), where we also study retail competition with salient‐thinking consumers.…”
Section: Introductionmentioning
confidence: 99%
“…(2016), Herweg et al. (2017), Helfrich and Herweg (2020), Apffelstaedt and Mechtenberg (2021), and Dertwinkel‐Kalt and Köster (2022). Notably, we share with the extant literature the result that such preferences can distort consumers' choices, prices, and ultimately firms' product choices.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it was shown that the presented model was 84% accurate in predicting quality. Another example was [17], in which customer decisions were supported by predicting changes in their decisions based on the quality and price of the product. Specifications dependent on customer choice (importance, focus, and relative thinking) and the decoy effect were compared, and it was determined that the decoy effect was similarly important to the price and quality of the product.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the product quality level can be predicted [14][15][16][17][18]. In addition, the impact of products on the natural environment can be predicted [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%